2014
DOI: 10.1056/nejmoa1411099
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Disease in the Democratic Republic of Congo

Abstract: The current EVD outbreak in the DRC has clinical and epidemiologic characteristics that are similar to those of previous EVD outbreaks in equatorial Africa. The causal agent is a local EBOV variant, and this outbreak has a zoonotic origin different from that in the 2014 epidemic in West Africa. (Funded by the Centre International de Recherches Médicales de Franceville and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
236
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(259 citation statements)
references
References 9 publications
14
236
3
6
Order By: Relevance
“…13 In any event, the magnitude of R 0 estimates for West Africa, calculated at an early stage of the epidemic, indicated that a sustained reduction in transmission of more than 50% (i.e., by a factor of more than 2) would be enough to eliminate infection from the human population. Even during a large epidemic, the elimination of Ebola virus from the human population is a feasible goal.…”
Section: Grow Th Of the Epidemicmentioning
confidence: 98%
“…13 In any event, the magnitude of R 0 estimates for West Africa, calculated at an early stage of the epidemic, indicated that a sustained reduction in transmission of more than 50% (i.e., by a factor of more than 2) would be enough to eliminate infection from the human population. Even during a large epidemic, the elimination of Ebola virus from the human population is a feasible goal.…”
Section: Grow Th Of the Epidemicmentioning
confidence: 98%
“…1 Secondly, the seventh reported outbreak of EVD in the Democratic Republic of Congo was less extended because the response was faster and more effective in this country and its neighbours. 16 …”
Section: Inadequate Health Care System In West Africamentioning
confidence: 99%
“…For example, 11% of Plasmodium falciparum-related deaths in sub-Saharan Africa occur in the DRC, 10 and the country experienced its seventh Ebola outbreak in August 2014. 11 …”
Section: General Settingmentioning
confidence: 99%